Rapid and Specific Genotyping System for Hepatitis B Virus Corresponding to Six Major Genotypes by PCR Using Type-Specific Primers - Naito, Hideo (American Society for Microbiology, 2001)
A simple and precise genotyping system based on PCR using type-specific primers was developed for the determination of genotypes A through F of hepatitis B virus (HBV). This assay system is considered to be a useful tool for the molecular diagnosis of HBV infection and for large-scale surveys.